2020
DOI: 10.1103/physreve.101.022603
|View full text |Cite
|
Sign up to set email alerts
|

Robust boundary flow in chiral active fluid

Abstract: We perform experiments on an active chiral fluid system of self-spinning rotors in confining boundary. Along the boundary, actively rotating rotors collectively drives a unidirectional material flow. We systematically vary rotor density and boundary shape; boundary flow robustly emerges under all conditions. Flow strength initially increases then decreases with rotor density (quantified by area fraction φ); peak strength appears around a density φ = 0.65. Boundary curvature plays an important role: flow near a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 55 publications
4
22
0
Order By: Relevance
“…The magnitude of the oscillation decays substantially as r decreases and vanishes far away from the boundary, indicating that the edge flow is localized near the boundary. Previous studies on the confined spinners also reveal the emergence of the edge flow, but with no oscillation (12,32,33).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The magnitude of the oscillation decays substantially as r decreases and vanishes far away from the boundary, indicating that the edge flow is localized near the boundary. Previous studies on the confined spinners also reveal the emergence of the edge flow, but with no oscillation (12,32,33).…”
Section: Resultsmentioning
confidence: 82%
“…Nevertheless, as a representative chiral active matter that breaks both parity and time-reversal symmetries, the active-rotor systems have recently been the subject of fundamental theoretical interest (30,31). It has been reported that a fluid of interacting rotors in confinement yields a collective edge flow parallel to the boundary (12,32,33), which is proven to be even topologically protected (34). In this case, the steric particle-boundary interactions impose a boundary condition that allows the conversion of spin-angular momentum into "orbital" angular momentum.…”
mentioning
confidence: 99%
“…A recent development in active matter concerns the use of chiral particles. Two classes of chiral particles may be identified with, first, the spinners [7][8][9][10][11][12][13][14], meaning rotating elements without directional motion, and second, the circling particles [15][16][17][18][19][20][21][22][23][24] combining directional and rotational activity.…”
Section: Sorting and Extraction Of Self-propelled Chiral Particles By Polarized Wall Currentsmentioning
confidence: 99%
“…Furthermore, we explicitly show the existence of exceptional edge modes in a more realistic system based on active matter 46 , which is a collection of self-propelled particles and has recently attracted much interest as a useful platform to study biological and out-of-equilibrium physics. Recent studies [47][48][49][50][51][52] have explored the existence of the edge modes in active matter protected by the bulk topology. Some of them 49,50,52 have utilized chiral active matter, which moves in a circular path or self-rotates.…”
mentioning
confidence: 99%
“…Recent studies [47][48][49][50][51][52] have explored the existence of the edge modes in active matter protected by the bulk topology. Some of them 49,50,52 have utilized chiral active matter, which moves in a circular path or self-rotates. Chiral active matter has been experimentally realized, for example, in bacteria 53 and artificial L-shaped particles 54 .…”
mentioning
confidence: 99%